The genus Anarsia Meyrick (Lepidoptera, Gelechiidae) in Laos, with description of a new species and ten new records of the genus - Park, Kyu-Tek; Bae, Yang-Seop (Zootaxa, 2018)
The genus Anarsia Zeller (Lepidoptera, Gelechiidae) in Laos is reviewed, with 11 species including one new species: Anarsia laosana sp. nov. Additionally another 10 species of the genus, namely, Anarsia choana Park, A. decora Li & Zheng, A. isogona Meyrick, A. kepensis Park, A. ovula Park and Ponomarenko, A. paraisogona Park and Ponomarenko, A. patulella (Walker), A. porthmisa Park, A. phortica Meyrick, and A. tricornis Meyrick, are reported for the first time from Laos. Photos of all recorded species are shown, and genitalia for the new species and two poorly known species, A. decora and A. paraisogona Park and Ponomarenko, are illustrated.